STUDI KELAYAKAN USAHA DAN ANALISIS SWOT SEBAGAI UPAYA DALAM MENGEMBANGKAN UMKM TEMPE UCUP DI KOTA SERANG - Fathurrohman, Muhammad Khaeru; Hadi, Abdullah; Aziz, Muhammad Faisal; Ahyakudin (Fakultas Ekonomi, Bisnis dan Humaniora, 2025)
Along with the competition of similar businesses in the market, UMKM Tempe Ucup began to feel that there was no significant increase (the same) in the production carried out every day. This study aims to analyze the feasibility study and SWOT analysis on Tempe Ucup MSME in Serang City. This type of research is descriptive qualitative research. Data collection is done through observation, interviews, and documentation. Non-financial and financial feasibility are part of the data analysis technique. The findings of this study indicate that Tempe Ucup MSME is not yet feasible in terms of legal and market aspects. However, in terms of financial aspects, it is considered feasible from the Profitability Index (PI) value of 6.93 > 1, which means it is profitable. SWOT analysis has been identified in the SWOT matrix of 4 strategies, namely Strengths-Opportunities (S-O), Weaknesses-Opportunities (W-O), Strengths-Threats (S-T), and Weaknesses-Threats (W-T). The business feasibility study and SWOT analysis are considered to be able to contribute positively to Tempe Ucup MSMEs in business development to face similar business competition in the market.